Diagnóstico ambiental participativo como ferramenta para a gestão territorial da terra indígena Kanindé de Aratuba/CE - Rabelo, Távila da Silva (2022)
The main objective of the work is the elaboration of an Environmental Diagnosis of the Indigenous Land (IL) Kanindé de Aratuba - CE, which, in addition to collaborating for the management of the IL, can contribute to a systematization of traditional knowledge about their lands, mixing them with scientific knowledge, focusing mainly on the physical characteristics of the territory and its connections with the indigenous people. The specific objectives address the understanding of the history of indigenous peoples in the Northeast; the identification of socioeconomic, historical, cultural and environmental aspects of the Kanindé indigenous population of Aratuba. The environmental characterization of the IL, with indication by the community of the main aspects of the territory, and the construction of the Environmental Diagnosis of the IL Kanindé of Aratuba/CE, was elaborated with emphasis on the physical aspects of the territory. Allied to a qualitative perspective, the methodological approach involved bibliographic research, field work to recognize the area and the presentation of the work proposal and approval by local leaders, and semi-structured interviews with three groups of the indigenous community: youth, teachers and leaders. The results range from the synthesis of the theoretical framework for understanding the issue, such as the history of the Kanindé indigenous people, and the actual Environmental Diagnosis, with the elaboration of maps that present the physical characteristics of the territory, and the discussion about the aspects socioeconomic. In addition to discussing the perceptions of the Kanindé indigenous people of Aratuba about their territory and the possible territorial management processes.